Effects of Tai Chi on the Executive Function and Physical Fitness of Female Methamphetamine Dependents: A Randomized Controlled Trial - Menglu, Shen; Ruiwen, Liu; Suyong, Yang; Dong, Zhu (Frontiers in Psychiatry, 2021)
PURPOSE: Exercise improves the health and mental status of drug dependents. The way by which Tai Chi (TC) as a special exercise treatment affects executive functions (EFs) of methamphetamine (MA) dependents is yet to be established. This study aimed to explore the effects of TC on the EFs and physical fitness of MA dependents. METHODS: A total of 76 female MA dependents were randomly assigned to the exercise and control groups. The exercise group underwent three 60-min sessions of TC training per week for 12 weeks. The control group was trained with conventional exercises including the 9th Guang Bo Ti Cao and square dance. Physical fitness and EF assessments that evaluated inhibitory control (IC, go/no-go task), working memory (3-back task) and cognitive flexibility (switching task) were performed at baseline and at 12 weeks. A repeated-measures ANOVA was applied to analyse the differences of group and time. RESULTS: The exercise group showed decreased response time (RT) with a significant main effect of time on the go/no-go task (F(1, 68) = 9.6, p < 0.05). The interaction effect between time and group was significant on accuracy (F(1, 61) = 4.73, p < 0.05), and the main effect of time was significant on RT (F(1, 61) = 4.66, p < 0.05) in the 3-back task of the exercise group. Significant changes in BMI (F(1,68) = 19.57, p < 0.05), vital capacity (F(1,68) = 6.00, p < 0.05) and systolic blood pressure (F(1,68) = 6.11, p < 0.05) were observed in the exercise group. CONCLUSION: These findings showed that 3 months of TC training can improve the IC and maintain the working memory and cognitive flexibility of MA dependents. Other data implied that TC may improve the physical fitness of MA dependents.